2013
DOI: 10.1002/ece3.872
|View full text |Cite
|
Sign up to set email alerts
|

The density and spatial arrangement of the invasive oyster Crassostrea gigas determines its impact on settlement of native oyster larvae

Abstract: Understanding how the density and spatial arrangement of invaders is critical to developing management strategies of pest species. The Pacific oyster, Crassostrea gigas, has been translocated around the world for aquaculture and in many instances has established wild populations. Relative to other species of bivalve, it displays rapid suspension feeding, which may cause mortality of pelagic invertebrate larvae. We compared the effect on settlement of Sydney rock oyster, Saccostrea glomerata, larvae of manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Repeat estimates of oyster density (Doonan et al 1992, Michael et al 2001, and of dredge efficiency (the scalar used to estimate absolute abundance, Fu et al 2016) show good consistency in Foveaux Strait. Manipulative studies to investigate the effects of spawner density on recruitment have been undertaken for O. chilensis in Tasman Bay, New Zealand (Brown 2011), and elsewhere for C. gigas and Saccostrea glomerata (Wilkie et al 2013), and for the bay scallop Argopecten irradians (Tettelbach & Wenczel 1993, Peterson et al 1996. The effects of increased spawner density on recruitment were mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Repeat estimates of oyster density (Doonan et al 1992, Michael et al 2001, and of dredge efficiency (the scalar used to estimate absolute abundance, Fu et al 2016) show good consistency in Foveaux Strait. Manipulative studies to investigate the effects of spawner density on recruitment have been undertaken for O. chilensis in Tasman Bay, New Zealand (Brown 2011), and elsewhere for C. gigas and Saccostrea glomerata (Wilkie et al 2013), and for the bay scallop Argopecten irradians (Tettelbach & Wenczel 1993, Peterson et al 1996. The effects of increased spawner density on recruitment were mixed.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological impacts of invasive species are complex and context‐dependent (Thomsen et al , Wilkie et al ). Our study adds to a growing body of evidence that impact does not always increase proportionally with invader density (Thiele et al , Elgersma and Ehrenfeld ) and in the case of Kornis et al (), the relationship was counter‐intuitive, with decreased impact at high density.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have examined the density‐dependent ecological impacts of invasive species and they detected both linear and non‐linear relationships between population density and ecological impact (Li et al , Kulhanek et al , Thomsen et al , Green and Crowe , Kornis et al , Wilkie et al ). For example, Elgersma and Ehrenfeld () found that the cascading impacts of an invasive shrub (Japanese barberry Berberis thunbergii ) were linear on decomposition rates but non‐linear on microbial community structure.…”
mentioning
confidence: 99%
“…• Assessment of the size of the recently established population of Pacific oysters in the Swartkops River estuary, and continued surveillance in estuaries such as those of the Breede and Kaaimans rivers, where the species currently occurs, are management priorities. Manual eradication is recommended for these estuaries, given that early elimination of small populations is effective in preventing invasions (Wilkie et al 2013). The physical destruction of intertidal oysters [using crowbars] has proved successful in Australia (Anon.…”
Section: Conclusion: Recommendations For Aquaculture Policymentioning
confidence: 99%